Ethics Perspective of Quality Accounting Information and Future Certainty: A Pattern of Rationally Perceived Decision - Muljanto Siladjaja; Trinandari Prasetya Nugrahanti; Pamela Magdalena (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research tested the distinctive capability of detecting misleading information when real earnings have positively stimulated the smooth movement of the market price. Methodology/approach: This causal research used the primary data from the investor community in 2022, which amounted to 3.242 respondents for running SEM and endogeneity testing; FGD has been the fittest validation process for capturing the rationality models. Findings: High consistency of integrity-characteristic played a crucial role in designing a prudent accounting treatment which indicates the ethics code related to highly sustainable business during an uncertain future global economy. Inevitably, a measurement of trust in high earning quality pointed out that this quality measurement is to protect this investment decision in a highly secured, safe area. Practical implications: One centralized platform of financial reporting services should support the attractiveness of obedience and compliance as an incomparable advantage of positive earnings management. High-prospected firms should be assessed by high-quality accounting information; the delisting procedure has been prioritized firmly for low-prospect ones.  Originality/value: This research explores the pattern of predictive simulation modeling as the existence of game theory, adapted from simplex-linear programming; this rationality model has strengthened as a fundamental requirement to illustrate high future certainty.